Public Perception of a Mining Company’s Instagram Account as a Sustainable Enterprise (Case Study of the Instagram Account @agincourtresources) - Amanda, Mutia; Batubara, Abdul Karim (Borong Newinera Publisher, 2025)
This study aims to examine public perception of sustainability communication carried out through the Instagram account of PT Agincourt Resources, as part of the company's efforts to establish a sustainable image in the digital era. Using a descriptive quantitative approach, a survey was conducted involving 100 followers of the Instagram account @agincourtresources. Public perception was analyzed based on six indicators from McGuire’s model: presentation, attention, comprehension, acceptance, retention, and behavior. The findings reveal that the average public perception score is 75.3%, with the indicators of message acceptance and retention reaching very high categories (82.6% and 84.5%, respectively). However, the behavior indicator scored only 59.8%, indicating a need to enhance active follower engagement. These findings suggest that while sustainability messages are well understood and accepted, active participation remains suboptimal. The practical implication of this study highlights the importance of strengthening interaction-based digital communication strategies, such as leveraging Instagram features and educational content, to foster active engagement and reinforce the company’s sustainable image.